Spectrophotometric Determination of Sodium Sulfacetamide Using Pyrocatechol as an Oxidative Coupling Agent - Marib Ismail Ali; Israa Talib Humeidy (Indonesian Journal of Chemistry, 2024)
Oxidative coupling reaction is one of the simplest and fastest spectrophotometric methods for measuring sodium sulfacetamide (SCS) in pure formulations and pharmaceutical formulations (eye ointment) when compared to other methods that require difficult and costly operating conditions. Here, a new approach for quantifying SCS drug spectrophotometrically by oxidative coupling was described. The research is based on the oxidation of the drug with potassium periodate and then conjugation with pyrocatechol reagent in the neutral medium, which results in a water-soluble and stable reddish-brown product that had an absorption band at 500.5 nm. In this work, oxidant agent quantity, coupling reagent quantity, oxidation time, temperature effect, stoichiometry between SCS and pyrocatechol, interference effect, and calibration curve were all studied. Beer's law linearity ranged from 6.25–112.5 µg mL−1. The molar absorptivity, Sandell’s index, detection limit, determination coefficient, and average recovery percentage were 5185.7 L mol−1 cm−1, 0.049 μg cm−2, 0.0889 µg mL−1, 0.9988, and 100.34% respectively. The determination of sulfacetamide in pharmaceutical preparation eye, ointment was successful using this method.